History of Islamic Civilization in the West Asian Region: Tracking the Roots of the Palestine-Israel Conflict - 'Afifah, Nurul; Susanti, Nelvi; Soraya, Lusi (Nur Science Institute, 2024)
This article discusses Islam in West Asia, focusing on religious patterns, culture, economic dynamics, politics, and the conflict in Palestine. It aims to provide insights into West Asia to deepen understanding of the region and issues related to the ongoing conflict in Palestine, including the roles of various actors. Using the Systematic Literature Review (SLR) method and a descriptive qualitative approach, this article reveals that West Asia, with its strategic location, has a rich history of cultural and religious diversity. This diversity is reflected in the social, political, and economic systems of societies reliant on trade, agriculture, and livestock farming. The social and political structures of West Asian societies before Islam were marked by tribal and clan fanaticism, which underwent significant transformation with the arrival of Islam, promoting unity and structured governance. The conflict in Palestine exemplifies the political and social complexities in this region. Support from Shia groups like the Houthis and Hezbollah for the Palestinian struggle against Israel has led to various assumptions and interpretations. This article emphasizes the importance of international assistance to support the Palestinian struggle, alleviate the suffering of its people, and highlights the need for a multidimensional approach to understand and address existing conflicts.